Mesoscopic modeling and characterization of the porous electrodes for vanadium redox flow batteries - Li, Min; Bevilacqua, Nico; Zhu, Lijun; Leng, Wengliang; Duan, Kangjun; Xiao, Liusheng; Zeis, Roswitha; Sui, Pang Chieh (Journal of Energy Storage, 2020)
Porous electrodes are commonly used in electrochemical devices such as fuel cells and vanadium redox flow batteries (VRFBs). The performance of these electrodes depends on their transport properties including diffusivity, permeability and electric/thermal conductivities, and further on their surface properties if two-phase flow occurs at high current conditions. This paper reports a pore-scale investigation on the transport processes involved in a carbon felt for VRFB applications. The microstructure of a carbon felt over a range of compression ratios is first reconstructed from micro-computed tomography. Pore-scale model simulation, which solves the coupled transport of electrolyte in porous materials, is employed to compute the effective transport properties of the reconstructed model. The permeability and diffusivity of the carbon felt are found to decrease with increasing compression ratio. Transport of liquid water within the reconstructed carbon felt is studied based on the multiple-relaxation-time lattice Boltzmann method and the simulation result indicates that compression on the electrode causes a large drop in porosity and flow resistance increases accordingly. Furthermore, the reconstructed model is converted to a finite-element model and then solid mechanics simulations are performed to gain insight to the stress distribution of the microstructure under compression. These effective transport properties are used in a two-dimensional macroscopic model to demonstrate the mesoscopic-macroscopic approach. Compression on a porous electrode is found to contribute notably on the increase of vanadium concentrations and pressure drops, which can be beneficial to the performance of VRFB. The methodology developed from this research is readily applicable to other porous electrodes such as the gas diffusion layers for fuel cells.
CRIS-Team Scopus Importer:2023-08-01
Keywords: Effective transport properties; Pore-scale model; Redox flow battery; X-ray micro-computed tomography